2004
DOI: 10.1038/sj.onc.1207917
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated mda-7 expression suppresses DNA repair capacity and radiosensitizes non-small-cell lung cancer cells

Abstract: The melanoma differentiation-associated gene-7 (mda-7) was identified by virtue of its enhanced expression in human melanoma cells induced into terminal differentiation. Enforced expression of mda-7 in human cancer cell lines of diverse origins results in the suppression of growth and induction of apoptosis. We have shown that adenoviral-mediated mda-7 (Ad-mda7) radiosensitizes non-small-cell lung cancer (NSCLC) cells by enhancing the apoptotic pathway. To identify the mechanism of this radiosensitization, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 82%
“…[18][19][20][21][22][23]38 It is now known that mda-7 activates various signaling pathways in a cell-type-specific manner, and that these pathways ultimately converge on mitochondrial destruction and induction of apoptosis. 21,22,[24][25][26][27][28][29][30] However, in spite of its clear tumor-suppressive effects, the mechanisms by which Ad-mda7 induces cytotoxicity have not been fully characterized. Our group has previously demonstrated that Ad-mda7, as a single agent therapy, induces apoptosis and inhibits growth in pancreatic, lung and breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…We updated this relatively old approach (20) to incorporate expression of a reporter gene as the readout; radiation-induced DNA lesions in the reporter gene must be repaired by the host cell with complete fidelity in order for functional gene expression to be restored. We have shown previously that this modified assay detects deficiencies in cellular DSB repair capacity (21). The results of our host cell reactivation assays (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The adenoviral vector required a high dose of radiation because of its small genome size compared with a mammalian cell. Our calculations indicate that 4,000 Gy should induce about 1 to 2 DSBs/vector particle (21). This is based on the target size of the vector genome (3.5 Â 10 4 bp) versus that of the mammalian cell (3 Â 10 9 bp) and using the value of 35 for the DSBs induced per Gy in the mammalian genome.…”
Section: Methodsmentioning
confidence: 99%
“…To detect high molecular weight DNA fragmentation, genomic DNA in the CO-3 tumor cells was extracted and purified using a Get pure DNA kit, loaded with exactly 1.2% agarose and 10 µg of DNA in each well; the DNA was then separated using pulse field gel electrophoresis (PFGE) using a CHEF-DR II system (Bio-Rad Laboratories, Tokyo, Japan) at 1.5 V/cm for 20 h at 25˚C in 0.5X TBE buffer as previously described (11). A comparison of the DNA concentrations among the different samples was performed using ethidium bromide staining.…”
Section: Methodsmentioning
confidence: 99%